Is irrigation water free?: a reality check in the Indo-Gangetic Basin - Shah, Tushaar; Ul-Hassan, Mehmood; Khattak, M.Z.; Banerjee, Partha Sarathi; Singh, Om Prakash; Ur Rehman, S. (2009)
'Getting prices right? is the silver bullet widely advocated to developing countries in fighting waste, misallocation and scarcity of water. In the vast, poverty-stricken Indo-Gangetic basin, however, high surrogate water price is driving out small-holder irrigation. With rising diesel prices, most small-holders who use borewells for irrigation find effective water use cost soaring, obliging them to economize on water use even by quitting irrigated farming. Electrified borewell owners, far fewer, face low marginal cost but have to contend with stringent electricity rationing. Public irrigation systems grossly under-price irrigation, but these are getting marginalized despite massive government and donor investments.